2013
DOI: 10.1107/s0907444912046690
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the role ofBacillus subtilisYwfH (BacG) in tetrahydrotyrosine synthesis

Abstract: The synthesis of the dipeptide antibiotic bacilysin involves the sequential action of multiple enzymes in the bac operon. YwfH (also referred to as BacG) catalyzes the stereoselective reduction of dihydro-hydroxyphenylpyruvate (H2HPP) to tetrahydro-hydroxyphenylpyruvate (H4HPP) in this biosynthetic pathway. YwfH is an NADPH-dependent reductase that facilitates the conjugate addition of a hydride at the C4 olefin terminus of H2HPP. Here, the structure of YwfH is described at three conformational steps: the apo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The latter one seemed of special interest in a strain that had survived and overcome other competitors in a controlled environment. Among the 12B3-5 entries in this category, there were several peptides with antimicrobial activity like BacG protein [29], involved in the synthesis of the non-ribosomally synthesised dipeptide antibiotic produced by Bacillus subtillis; the E. faecalis macrolide-efflux protein A [30], able to regulate internal macrolide levels; or the PcfF protein, an accessory factor necessary to initiate the transfer of the tetracycline resistance plasmid pCF10 [31]. pCF10 is a member of a family of E. faecalis pheromone-inducible conjugative plasmids, which are determinants for ecological relations and strain communication in the gut environment, contributing to the GI tract competitive fitness [32].…”
Section: Discussionmentioning
confidence: 99%
“…The latter one seemed of special interest in a strain that had survived and overcome other competitors in a controlled environment. Among the 12B3-5 entries in this category, there were several peptides with antimicrobial activity like BacG protein [29], involved in the synthesis of the non-ribosomally synthesised dipeptide antibiotic produced by Bacillus subtillis; the E. faecalis macrolide-efflux protein A [30], able to regulate internal macrolide levels; or the PcfF protein, an accessory factor necessary to initiate the transfer of the tetracycline resistance plasmid pCF10 [31]. pCF10 is a member of a family of E. faecalis pheromone-inducible conjugative plasmids, which are determinants for ecological relations and strain communication in the gut environment, contributing to the GI tract competitive fitness [32].…”
Section: Discussionmentioning
confidence: 99%
“…BacG (YwfH) is a NADPH-dependent reductase for stereoselective reduction of 3E-and 3Z-ex-H 2 HPP to tetrahydrohydroxyphenylpyruvate (H 4 HPP) 4R-and 4S-diastereomers which are then acted on by BacF and converted to corresponding H 4 Tyr diastereomers [35]. BacG structure was described at three conformational steps, providing a rationale for the ping-pong reaction mechanism [41]. BacF catalyzes reductive amination of the 2-keto group of the anticapsin candidate by using L-phenylalanine as an amino group donor [35].…”
Section: Biochemistry and Genetics Of Bacilysin Biosynthesismentioning
confidence: 99%
“…Subtilosin A and bacilysin participate in biocontrol efficacy of B. subtilis 9407 against BFB The synthetic genes srfAB, sboA, and bacG are essential for the synthesis of surfactin, subtilosin A, and bacilysin, respectively (Zheng et al 2000;Stein 2005;Rajavel et al 2013). Our previous studies showed that a lack of srfAB decreases surfactin production and colonization ability of B. subtilis 9407, thereby decreasing its biocontrol efficacy against BFB (Fan et al 2017b).…”
Section: Prediction Of Biosynthesis Gene Clusters In the Genome Sequence Of B Subtillis 9407mentioning
confidence: 99%